A DISPLACEMENT-BASED SEISMIC DESIGN METHOD FOR FRAMED STRUCTURES INVOLVING SIDESWAY-COLLAPSE PREVENTION - López Ríos, Saúl Esteban (My University, 2015)
Reference SDOF system; displacement-based seismic design; sidesway collapse; P-Delta effects
Keywords: Reference SDOF system; displacement-based seismic design; sidesway collapse; P-Delta effects